Wage Differentials and Employment Choice of Chinese Rural‐Migrant and Urban‐Resident Workers. (December 2015) - Cui, Yuling; Nahm, Daehoon; Tani, Massimiliano
Abstract: This article investigates the determinants of the wage rates and the drivers of the decision to be self‐employed for two distinctive groups in the Chinese economy: rural‐migrant and urban‐resident workers. Employing the endogenous switching model, it addresses the issues of selectivity and the endogeneity of wage differentials. Results show that the factors that determine wages and the decision to enter self‐employment are significantly different between the migrant self‐employed, migrant paid‐worker, urbanite self‐employed and urbanite paid‐worker groups. Evidence indicates that a large proportion of workers are not in the type of job in which they could earn the best wage.